Agricultural machinery service provision business: A business model for return migrant workers - Prajapati, Ashta (Cereal Systems Initiative for South Asia, 2021)
Agricultural machinery service provision businesses at the individual level, providing services for crop production, harvesting, post-harvest operations, processing, and transportation, is a somewhat new concept in the context of Nepal. Most of these service provision businesses are owned and managed by the same person. Managing a service provision business means overseeing a hire service with a primary business orientation, unlike, for example, a farmer with a machine who additionally provides services to neighbors. This orientation helps to ensure that activities and tasks are completed effectively and efficiently.